Developing Sino- Israeli Relations in the Post-Cold War Era: Analyzing Desecuritization Scenarios for Iran - A. P. Fariborz; J. S. Seyed; A. Hossein (Vestnik MGIMO-Universiteta, 2020)
An important feature of Israel's foreign policy in the post-Cold War era has been development of relations with emerging powers, including China. The importance of the economic component in the foreign policy of both countries, China's efforts to achieve the status of a great power, and Israel's strategies to improve its global image and regional position have brought the two countries' relations into a form of comprehensive cooperation in the post-Cold War era. Describing the relations between the two countries in the political, military and economic spheres and acknowledging the impact of China and Israel's behavior patterns on national and regional security of Iran the article seeks to answer the following questions : What are the indicators of the development of China-Israel relations in the post-Cold War era? What are the consequences of these relations for Iran? From this article's point of view, the development of China-Israel relations in all areas has been on an upward trajectory and hence have substantial implications at the national (threatening China-Iran relations in the field of energy and weakening Iran-China military relations and enfeebling Iran's position in the Silk Road project), regional (changing the balance to the detriment of Iran, Iran's containment and normalization of Arab-Israeli relations) and international levels (China's accompanying pressures on Iran, Israel's use of China's capacity in international institutions and efforts to legitimizing and reinforcing the notion of Iran's threat and continuing Iranophobia) for Iran's security.